Pengenalan Aplikasi SmartPLS Bagi Mahasiswa Baru Program Studi Magister Manajemen Universitas Pattimura - Walter Tabelessy; Jozef Ricky Pattiruhu (Communio: Jurnal Pengabdian Kepada Masyarakat, 2022)
This introductory activity aims to educate new students of the Pattimura University Master of Management Study Program so that they have one perception and increase understanding of the concepts and stages of data processing using the SmartPLS application and will ultimately improve the ability to process data. In this activity, the method used is interactive learning, namely the use of computers as online learning media. Submission of material is carried out in the form of lectures, accompanied by examples of using the SmartPLS application to students. The results of this activity have united different perceptions and increased student knowledge about the concepts and stages of data processing using this application. The Pattimura University Master of Management Program can realize this online introductory activity in the form of offline training so that it can immediately practice and evaluate the extent to which students understand how to process data using the SmartPLS application. Or use other SEM-PLS applications, for example the WarpPLS application.